문명, 개화의 계보와 분화(1876년~1905년) -개념의 의미화 과정을 중심으로 - 김윤희; Yun Hee Kim (史叢(사총), 0(79), 2013)
This paper looks into the process by which the notions of Gaehwa and civilization were bestowed the meaning through the media in order to consider the social trends in the period between late 19th century and early 20th century which are represented as the period of Gaehwa. The changes in the meaning of notions which appear in the media can be the process of communication among the people influenced by both ``political empowerment which controls the media`` and the media. The notions of Gaehwa and civilization, which are used for political planning, have correlation with people`s sentiment toward the society, and in the process, form the meaning if the political planning of intellectuals aims to secure the justification for the decision-making by country through the mobilization of people. That is an incessant interactive process among the intellectuals and the people who can be embraced by the intellectuals. The terms, such as Gaehwa, civilization-Gaehwa, civilization, etc., which are used by intellectuals, have relationship with people`s sentiment, called the ``pubic mind``, and have the changing meaning, and at the same time, have functioned as the mechanism for mobilizing the people. The notions of civilization and Gaehwa have the changing meaning amid the political planning that aims to form modern ruling system supported by the interconnected twin pillars of the government and people since the basic rights of people were institutionalized by Gabo Reform.